Effects and mechanism of (Be/Mg/Ca) doping and point defects (VZn, Hi) on the p-type conductivity of ZnO: A first-principles study. (15th February 2022) - Qi, Mude; Hou, Qingyu; Li, Yong; Gu, Yulan; Yang, Airong
Abstract: A stable and reliable p-type ZnO semiconductor is difficult to obtain, because ZnO crystals have a hexagonal wurtzite structure, they have no center of symmetry, and the c-axis direction exhibits polarity. The preparation of ZnO materials by using growth techniques, such as metal–organic chemical vapor deposition or hydrogenated vapor phase epitaxy, will produce a large amount of H interstitial, that is difficult to remove. To solve this problem, we applied the generalized gradient approximation method and performed density functional theory in this work, to study the influences of Be/Mg/Ca single doping and the coexistence of Zn vacancies and H interstitial on the conductivity of ZnO. This study found that the formation energy of Zn34 MHi O36 (M = Be/Mg/Ca) system is lower than that of the doped system the Zn34 MO36 (M = Be/Mg/Ca), and the formation energy of Zn34 BeHi O36 is the smallest. The hole mobility and conductivity of all the doped systems parallel to the c-axis direction are larger than those of the systems parallel to the a-axis direction. Among them, the hole mobility and conductivity of the Zn34 CaHi O36 system are the largest. This study exerts a guiding effect on the design and preparation of new p-type ZnO conductive functional materials. Highlights: Mobility of Zn34 CaHi O36 are the best.Doped systems are p-type degenerate semiconductors.Doped systems are stable.